Generation and Analysis of Human and Murine Osteoclasts. (8th April 2019) - Steffen, Ulrike; Andes, Fabian T.; Schett, Georg
Abstract: Osteoclasts are the only bone‐resorbing cells in the body. Together with bone‐forming osteoblasts, they are responsible for bone homeostasis and constant bone remodeling. Aberrant activation of osteoclasts leads to bone loss, as seen in postmenopausal osteoporosis or in autoimmune diseases like rheumatoid arthritis. Although much research has been performed to understand and prevent osteoclast‐mediated bone loss, the mechanisms of osteoclast hyperactivation are not completely understood. This unit describes several protocols for ex vivo generation of murine and human osteoclasts, allowing study of the effects of specific cells, cytokines, or chemical substances on osteoclast formation and activity without the need for expensive and time‐consuming animal experiments. In addition, we provide protocols for specific staining of osteoclasts and for analysis of resorption activity using calcium phosphate–coated surfaces or bone slices. © 2019 by John Wiley & Sons, Inc.